Hypogastric Artery Occlusion with Evoked Potentials Monitoring as Bailout Technique to Assess the Risk of Postoperative Spinal Cord Ischemia - D'Oria, Mario; Calvagna, Cristiano; Chiarandini, Stefano; Ziani, Barbara (AORTA, 2019)
A 65-year-old man, with previous open surgical repair of an infrarenal abdominal aortic, presented with acute complicated (paraplegia) Type B aortic dissection. He successfully underwent endovascular repair of the descending thoracic and abdominal aorta. Following the procedure, the neurological manifestations resolved. As he had a concomitant aneurysm of the right hypogastric artery (HGA), we executed a 10-minute balloon occlusion of this artery with evoked potential measurements to assess the risk of spinal cord ischemia after exclusion of the right HGA. The examination was interpreted as negative, and we proceeded with coil embolization of the right HGA and subsequent placement of an endograft landing distally within the external iliac artery. The postoperative course was totally uneventful, and the patient was discharged home 4 days after the operation. Computed tomography angiography follow-up at 1, 6, 12 and 24 months showed patency of all endografts without any signs of endoleak and effective remodeling of the descending thoracic aorta with volume reduction of the false lumen.
Keywords: hypogastric artery; spinal cord ischemia; endovascular aortic surgery; acute aortic dissection; evoked potentials